Honey, a gift from nature to health and beauty: a review - Ab. Hadi, Hazrina; Syed Omar, Sharifah Shakirah; Awadh, Ammar Ihsan Jawad (University of Huddersfield Press, 2016)
Benefits of honey are contributed by the composition of its elements such as glucose, fructose, glucose oxidase, vitamins and phenolic compounds. For health, honey can be used to treat wounds due to the antibacterial activity conferred by the hydrogen peroxide produced by glucose oxidase in honey. Anti-inflammatory, anti-oxidant, deodorizing and tissue regeneration activities in honey also help in the wound healing process. It can also be an alternative sweetener for diabetic patients to ensure compliance to a healthy diet. Moreover, honey exerts several effects such as lowering low density lipids and increasing high density lipids, thus reducing risk of atherosclerosis. In terms of beauty, honey can be used on skin and hair. It moisturizes skin through its natural humectant properties contributed by high contents of fructose and glucose. Honey treats acne on the skin due to its antibacterial activity, anti-inflammatory action and tissue repair. The hair can benefit from honey in such a way that the hair has abundance, and becomes easier to comb. However, there have not been as many studies regarding the use of honey in skin in comparison to its use for health. Therefore, future studies on honey could research its use, action and benefits in both cosmetics and dermatology.